Exigências térmicas de Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae) - Albergaria, Nuno M. M. S. [UNESP]; Cividanes, Francisco J. [UNESP] (My University, 2002)
The development (egg-adult) of Bemisia tabaci (Genn.) B-biotype (=Bemisia argentifolii, Bellows & Perring), was studied in field conditions and in incubators at constant temperatures (15, 20, 25, 30 and 35±1°C), using soybean, Glycine max (L.) Merrill, Msoy 8001, as host plant. The temperatures threshold (Tb) and the thermal constant (K) for egg, nymph and life cycle (egg-adult) were 11.1°C/ 98.8 degree-days; 6.8°C/383.8 degree-days and 8.3°C/472.6 degree-days, respectively. At the temperatures of 15°C and 35°C, insect viability was smaller. In the field, 70% of the adults emerged after 413,2 degree-day were accumulated. The degree-day pattern used was adequate for the previewing Bemisia tabaci B-biotype adult occurrence in field, and it can also be used to determine the number of generations in different areas of the country.
Thermal requirements of Bemisia tabaci (Genn.) B-biotype (Hemiptera: Aleyrodidae)
Keywords: Bemisia argentifolii; Degree-day; Glycine max; Soybean; Temperature; Whitefly